Effects of cannabidiol on AMPKα2 /HIF-1α/BNIP3/NIX signaling pathway in skeletal muscle injury - Zhiquan Hou; Zhifang Wang; Jun Zhang; Yunen Liu; Zhonghua Luo (Frontiers Media S.A., 2024)
Cannabidiol: (CBD) is a non-psychoactive natural active ingredient from cannabis plant, which has many pharmacological effects, including neuroprotection, antiemetic, anti-inflammatory and anti-skeletal muscle injury. However, the mechanism of its effect on skeletal muscle injury still needs further research. In order to seek a scientifically effective way to combat skeletal muscle injury during exercise, we used healthy SD rats to establish an exercise-induced skeletal muscle injury model by treadmill training, and systematically investigated the effects and mechanisms of CBD, a natural compound in the traditional Chinese medicine Cannabis sativa L., on combating skeletal muscle injury during exercise. CBD effectively improved the fracture of skeletal muscle tissue and reduced the degree of inflammatory cell infiltration. Biochemical indexes such as CK, T, Cor, LDH, SOD, MDA, and GSH-Px in serum of rats returned to normal. Combining transcriptome and network analysis results, CBD may play a protective role in exercise-induced skeletal muscle injury through HIF-1 signaling pathway. The experimental results implied that CBD could down-regulate the expression of IL-6, NF-κB, TNF-α, Keap1, AMPKα2, HIF-1α, BNIP3 and NIX, and raised the protein expression of IL-10, Nrf2 and HO-1. These results indicate that the protective effect of CBD on exercise-induced skeletal muscle injury may be related to the inhibition of oxidative stress and inflammation, thus inhibiting skeletal muscle injury through AMPKα2/HIF-1α/BNIP3/NIX signal pathways.